PENGAMANAN DATA ABSENSI MENGGUNAKAN RSA BERBASIS ANDROID PADA PT. ARKONIN - Farhana Nabila, (2021)
ttendance is one of the important performance appraisals. To facilitate attendance in a field project, attendance is needed that can support data collection in a field project. PT. Arkonin is one of the providers of development consulting services. Currently there is an attendance system in the form of a fingerprint but there are some problems in the attendance, namely employees who work on field projects must send attendance data via email to the company. The purpose of this study is to secure the process of sending data for employee attendance in the field project section to the company by usingattendance technology fingerprint on android using the RSA algorithm method, in this study discusses data security that is carried out for attendance, namely by carrying out the process of sending data in the form of encryption inside Android-based attendance application and the data is automatically sent to the database in the form of encryption and description data. System coding is done using Java, PHP, and MySQL. The design applies the OOAD (methodObject Analysis and Design) with the tools (UML) Unified Model Language. The results of this study are an Android-based attendance data security application, to facilitate attendance who works in field projects so that data is safe and fast to reach the relevant parties. From the description above is expected to provide the original attendance data.